Penerapan SAK EMKM Dalam Menyusun Laporan Keuangan UMKM Di CV. Putra Jaya Mandiri Pekanbaru: Penerapan SAK EMKM dalam laporan keuangnan - Melati, Syansi Melati Putri (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
This research was conducted based on the phenomenon that MSME registered in Cv. Putra Jaya Mandiri Pekanbaru are developing MSME that should prepare their financial statements based on SAK EMKM. However, in its implementation, it experienced obstacles in preparing financial statements based on SAK EMKM. This study aims to determine and examine the obstacles faced by MSME actors in preparing their financial statements based on SAK EMKM and designing a simple financial reporting system based on SAK EMKM. This research uses a qualitative approach using the case study method. The data sources used are primary data and secondary data. The method of data collection is carried out by means of interviews, documentation and observation. The results of the study show that in the preparation of financial statements MSME actors registered in Cv putra jaya mandiri pekanbaru have not implemented SAK EMKM because business actirs have never received socialialization, lack of educational background of MSME actors, none regulations related to the implementation of SAK EMKM, lack of knowledge and understanding related to SAK EMKM, lack oftraining SAK EMKM, low capital to employ expert staff in preparing financial statements and facilities inadequate infrastructure and business owners who do not focus on reporting their business results . Therefore, in this study, a simplefinancial reporting system was designed that can help MSME actors understand the context of preparing financial statementsbased on SAK EMKM.